Enhancing distance learning for non-sighted and visually impaired design students: a study on the usability and effectiveness of haptic tools - Esam, Asrizam; Nordin, Mohd Norazmi; Muhd Feisal Ismai, Albert Feisal; Mhd Khotib, Nor Aina; Bahaman, Muhamad Abrar; Maizan, Siti Hajar; Abbas, Mohd Saleh (UK Zhende Publishing, 2024)
In the realm of design education, catering to the needs of non-sighted and visually impaired students poses unique challenges, particularly in distance learning environments. This study investigates the usability and effectiveness of a specially designed haptic tool tailored to the needs of such students. The participants, comprising non-sighted and visually impaired design students enrolled in distance learning programs, were recruited through purposive sampling techniques, ensuring diverse perspectives and experiences. Data were collected through focus group discussions, in-depth interviews, and structured surveys, providing both qualitative and quantitative insights. Results indicate that the haptic tool received positive usability ratings, with participants acknowledging its effectiveness in facilitating understanding of visual concepts commonly encountered in design education. Additionally, participants reported perceived benefits including enhanced understanding of visual concepts, improved engagement in design tasks, facilitated collaboration with peers, and increased confidence in design abilities. However, challenges such as technical issues, learning curve, limited customization options, and accessibility barriers were also noted, suggesting areas for improvement in haptic tool design and implementation. Furthermore, correlations between participants' prior experience with haptic technology and usability ratings indicate the potential benefits of familiarity with tactile feedback systems in enhancing user interaction and satisfaction. Overall, this study underscores the importance of integrating haptic technology into distance learning environments to better support the learning needs of non-sighted and visually impaired design students, while also highlighting avenues for further research and development in this domain.